Nitrate Removal from Waste-Water Using Silica Nanoparticles - Phuong Kim To; Hoa Thai Ma; Lam Nguyen Hoang; Tan Tai Nguyen (Journal of Chemistry)
This work presented the removal of nitrate ions in aqueous solution based on silica nanoparticles (SiNPs), which were extracted from rice husk ash. The optimal conditions for nitrate ion adsorption were studied including pH, contact time, adsorbate concentration, and amount of absorbance. The surface morphological analysis showed that the SiNPs extracted (purity of 98%) were around 50 nm with a surface area of 30 m2·g−1 and adsorption average pore width of 2.72 nm, offers possibility for high capability of nitrate ion removal. The experimental results showed that the nitrate ion capability of adsorption was obtained around 14.22 mg·g−1 with a concentration range from 0 to 25 mg·L−1 based on optimizing conditions including pH 6, contact time of 50 minutes, and SiNP dosage of 0.15 g vol−1. In addition, nitrate ion removal based on SiNPs will provide considerate benefits such as the reducing costly sample pretreatment steps, less time-consuming, and reliable methods for processing nitrate-polluted water.